Predictors Of Relationship Quality And Relationship Outcomes In Midscale Restaurants In Izmir, Turkey - USTA, MURAT (International Journal of Contemporary Economics and Administrative Sciences, 2017)
This study analyzes the relationship management in the hospitality industry. There are three main constructs: relationship management activities (predictors), relationship quality and relationship outcomes (commitment, loyalty and word of moth). In this field there are a lot of researches, but this three constructs have not fully explored yet. A conceptual model was developed and tested to examine the mediating effect of relationship quality on the relationship between the seven relationship management activities and the three relationship outcomes. A detailed analyze from the survey made in 14 restaurants with 528 participants and 426 clean data shows that the relationship quality is the primary mediating construct between relationship management activities and relationship outcomes. The effective use of a relationship management strategy may increase customer commitment, spread positive word of mouth, and generate loyalty. The findings of this study provide restaurant managers with a guideline for developing and implementing an enhanced relationship management strategy.